Beberapa Aspek Biologi Parasitoid Apantheles sp pada Inangnya, Spodopera litura, Fab. setelah Perlakuan Ekstrak Daun dan Ranting Aglaia odorata (Lour) - Tarwotjo, Udi (Bioma : Berkala Ilmiah Biologi, 2015)
The objectives of this study were to evaluate effect of leaf and branch extract of the Aglaia odorata against:  emergences of adult Apantheles sp emerged from S. litura larvae, (2) the extract effect to live cycle and reproduction of  Apantheles sp (3) and its effect against the  morphology character some of parasitoid. The metode was used by of leaf-dip method. The leaf and branch effectivity bioassay used by of Ricinus communis leaf . The leaf disk were dipped in the extract solution on six concentration  for 10 s, and air dried. Each leaf disks was placed  six bottles glass and ten larvae were placed in each botlle, each concentration was replicated four time. Data collected  were subjected an anaysis of variance followed by mean comparation based of Duncan´t New Multiple Range Test. The imago Apantheles sp. emerged from host, S.  litura larvae was recorded of live cycle, its reproduction, and morphology character. The result showed that the length of pre adult stage of emerging parasitoids from of S.  litura larvae treated with 85,99 ppm was 45 percent, and with 21,95 ppm was 22,22 percent. The extract toxicity to natural enemies such as parasitoids relatively non toxis. The live cycle of female adult parasitoid was 16,90 and 6,20 days. Reproduction capacity of adult female parasitoids of 85,99 mg/L was 69,4 eggs/adult, which was statistically different from control, whereas of 21,95 treatment, it was 65,40 eggs/adult and its was not significant to control. Key words: Aglaia odorata, Lour, Spodoptera litura,, morphology character, Apanteles sp